Redefining the Metabolic Syndrome in Africa: A Systematic Review between 2005 and 2022 - Mabel A. Charles-Davies; Olulope O. Ajayi (Dubai Diabetes and Endocrinology Journal)
Background: Metabolic syndrome (MS) is a global health challenge. Its prevalence is on the rise in the developing countries. A shift from the indigenous African diet rich in dietary fibre and micronutrients as well as sedentary lifestyle have been implicated in its aetiology. Currently, accurate definition and diagnosis of MS in Africa constitute a challenge as none of the different definitions recognized African-specific cut-off points for the different MS components. Summary: PubMed and Google databases were searched for studies between 2005 and 2022 that met the eligibility criteria of the study using expressions such as MS in Africans and components of MS in Africans. Key Messages: Observations from this review showed that the current criteria for MS diagnosis are not definite for Africans. This review article, therefore, discusses the necessity to develop African-specific criteria for MS diagnosis, which will enhance its proper diagnosis and management in Africans.